¿CON QUÉ LIBROS SE APRENDERÍA FRANCÉS EN ESPAÑA EN 1808? - García Bascuñana, Juan F. (Anales de Filología Francesa, 2008)
Which books were used to learn French in Spain in 1808? Our study aims to analyse the books that Spaniards used to learn French in 1808, a crucial period in the history of Spain. It is not restricted, however, to these books. It also considers literary works that were also used to teach and disseminate the French language. Of particular importance among these works was Telemachus by Fénelon, which was used for the study of French and other purposes (pedagogical, philosophical, political, etc.), and also had intrinsic value as a literary work. Very few “French books” were actually published in Spain in this year, largely because of the complex political situation so, although our focus is 1808, we shall also consider the years both before and after this key moment.